Relationships Among Terminal Traits and Sale Prices of Red Angus Bulls Sold at Auction From 2017 Through 2019 - M. J. Smith; K. E. Fike; M. E. King; E. D. McCabe; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of this study was to evaluate the influence of terminal traits in the form of selection indices and expected progeny differences on the sale price of Red Angus Bulls sold at auction from 2017 through 2019 across the United States. Study Description:Information describing factors about Red Angus bulls marketed through auctions were obtained from the Red Angus Association of America (Commerce City, CO) in an electronic format. Data were collected for 21,362 Red Angus bulls offered for sale from 2017 through 2019. Multiple regression models were developed using backward selection procedures to examine the effect of terminally-related genetic factors in the form selection indices and expected progeny differences on bull sale price. Results:Various terminal factors in the form of selection indices and expected progeny differences were significant factors influencing Red Angus bull sale price. Sale price was found to be positively associated with GridMaster Index. Results indicated significant relationships between sale price and various expected progeny differences including birth weight expected progeny difference, marbling score expected progeny difference, carcass weight expected progeny difference, ribeye area expected progeny difference, and 12th rib fat thickness expected progeny difference. However, relatively low R2values across both models indicating that only a small amount of price variation was accounted for with these factors. Other factors likely affecting sale price were breeder reputation and visual aspects of bull quality. The Bottom Line:In addition to genetic factors, buyers may be considering other characteristics not captured within this data such as physical attributes, marketing tactics, and breeder reputation. Continued research and understanding of the various terminal factors affecting beef bull sale price may prove valuable to the beef industry.
Keywords: beef bulls; expected progeny differences; selection indices